Pengaruh Pendidikan Gizi dengan Media Booklet terhadap Pengetahuan dan Sikap Ibu Serta Asupan Protein dan Kalsium Anak Usia 1-3 Tahun Mengalami Stunting - Dini Lestrina; Oslida Martony (POLTEKKES KEMENKES MEDAN, 2021)
This study aims to determine the effect of nutrition education with booklet media on mother's knowledge and attitudes about stunting as well as protein and calcium intake for stunted children aged 1-3 years in Paluh Sibaji Village. This type of research is quasi-experimental with one group pre-post test design. The results showed that there was an increase in knowledge and attitudes of mothers about stunting, as well as children's protein and calcium intake. The average knowledge score before the intervention increased after the nutrition education intervention. In conclusion, the average intake of protein and calcium before the intervention increased after the nutrition education intervention with booklet media. Keywords: Calcium, Nutrition Education, Knowledge, Protein, Attitude, Stunting